Examining patterns of executive functioning across dimensions of psychopathology. (December 2022) - Roye, Scott; Calamia, Matthew; Robinson, Anthony
Abstract: Background and objectives: The current study examined relationships between psychopathology and individual domains of executive functioning (EF) amongst adults. While previous studies have examined these relationships using diagnostic groups, we compared factor structures of both dimensional psychopathology and EF and used an approach to better isolate EF-specific task variance within each domain. Methods: This study analyzed the data of 722 individuals between the ages of 18–59 years, who took part in the Nathan Kline Institute (NKI)-Rockland project. Confirmatory factor analyses were used to derive a three-factor model of EF (i.e., inhibition, shifting, and fluency) proposed by Karr et al. (2019) with scores primarily from the Delis-Kaplan Executive Function System (D-KEFS), as well as a three-factor model of psychopathology (i.e., internalizing, externalizing, and thought disorder symptoms) from the Adult Self-Report (ASR) and Peter's et al. Delusions Inventory (PDI). These models were compared using structural equation modeling. Results: Results demonstrated an adequate fit for both model structures and indicated that internalizing and externalizing psychopathology had positive and negative relationships with different factors of EF, while thought disorder traits were not related to EF. Limitations: This study examines pathological traits within a non-clinical sample that excluded individuals with severe mental illness. Additionally, analyses were limited by the availability of certain variables, and potential shared method variance within factors. Conclusions: Patterns of associations with EF were unique to all three aspects of dimensional psychopathology. When examined together, different dimensions of psychopathology were related to both better and worse EF performance. Highlights: Dimensional psychopathology emphasizes symptom severity over diagnostic categories. Executive functioning is a transdiagnostic feature of psychopathology. Non-executive functioning abilities can confound objective test performance. Understanding psychopathology and cognition can inform mental health treatment.